RENOVATED HOUSES AS OBJECTS OF TOURIST INTEREST IN EXCURSION TOURISM IN UKRAINE - HABA, Myroslava; KANDYBA, Svitlana (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article investigates the use of decorated houses, which can act as objects of tourist interest among travelers in excursion tourism in Ukraine. It is determined that the combination of the two industries of construction and tourism will contribute to the popularization of construction objects and their use in the organization of excursion activities and tourism. The TOP-5 houses that have been restored using modern innovative materials in Ukraine and which in the future can be objects of tourist interest in the organization of tourist trips and excursion activities are identified. In the current conditions of the war in Ukraine, excursion objects of domestic tourism are becoming increasingly valuable, in particular, various decorated houses deserve attention. However, there are buildings that can be objects of tourist interest in excursion tourism, but due to their unattractive aesthetic current appearance and the actual partial process of destruction do not have tourist value. This article is devoted to the issue of using various types of decoration of houses and premises and their involvement in tourist and excursion activities as objects of tourist interest in architectural excursions. An analysis of the labor intensity of various types of finishing works for cultural and domestic construction was carried out, which showed that the labor intensity of various types of finishing works for cultural and domestic construction is uneven. Existing theoretical approaches to the concept of excursion tourism and objects of tourist interest, which can be decorated houses, are considered. A study of decorated houses as possible potential excursion objects of tourist interest in Ukraine was conducted, which will contribute to attracting a larger number of travelers, expanding the range of tourist and excursion objects and satisfying their specific requests, which in turn will make it possible to increase the potential of less attractive tourist regions and make a profit, particularly in modern conditions.